Let-7i-5p Regulation of Cell Morphology and Migration Through Distinct Signaling Pathways in Normal and Pathogenic Urethral Fibroblasts - Zhang, Kaile; Yang, Ranxin; Chen, Jun; Qi, Er; Zhou, Shukui; Wang, Ying; Fu, Qiang; Chen, Rong; Fang, Xiaolan (Frontiers in Bioengineering and Biotechnology, 2020)
microRNAs regulate subcellular functions through distinct molecular mechanisms. In this study, we used normal and pathogenic fibroblasts in pelvic fracture urethral distraction defects (PFUDD) patients. PFUDD is a common disease that could severely affect patients’ life quality, yet little is known about the molecular mechanism associated with pathogenic fibrosis in PFUDD. Our data showed that let-7i-5p performs a multi-functional role in distinct signaling transduction pathways involved in cell morphology and cell migration in both normal and pathogenic fibroblasts. By analyzing the molecular mechanism associated with its functions, we found that let-7i-5p regulates through its direct target genes involved in collagen metabolism, cell proliferation and differentiation, TGF-beta signaling, DNA repair and ubiquitination, gene silencing and oxygen homeostasis. We conclude that let-7i-5p plays an essential role in regulating cell shape and tissue elasticity, cell migration, cell morphology and cytoskeleton, and could serve as a potential target for clinical treatment of urethral stricture patients.